Linear and non-linear optical properties of zinc borotellurite glass doped with erbium, erbium nanoparticles, neodymium and neodymium nanoparticles - Abd Azis, Muhammad Noorazlan (2016)
The multi-compositions of RE (Er2O3, Er2O3 nanoparticles, Nd2O3, Nd2O3 nanoparticles) doped zinc-borotellurite glass with chemical composition of {[(TeO2)0.70 (B2O3)0.30]0.7 (ZnO)0.3}1-y (RE)y, y = 0.005, 0.01, 0.02, 0.03, 0.04 and 0.05 were synthesized from high purity raw materials by using conventional melt quenching method. The physical, structural, linear and nonlinear optical properties of the glass system were characterized by using densimeter, X-ray diffraction (XRD), Fourier transform infra-red (FTIR), transmission electron microscopy (TEM), Ellipsometer, UV-Visible spectrophotometer, photoluminescence, and Z-scan technique. The amorphous nature of all the glass samples is confirmed by using X-ray diffraction (XRD) analysis. The presence of nonbridging oxygens in the glass network is obtained from FTIR analysis that formed as TeO3 and BO3 structural units. The presence of erbium nanoparticles and neodymium nanoparticles in the range 15 – 30 nm in the glass network are proved from TEM images. The values of density of the glass samples are found increases with increasing content of erbium (3.650 – 3.690 kg/m3), erbium nanoparticles (4.588 – 4.881 kg/m3), neodymium (3.672 – 3.931 kg/m3) and neodymium nanoparticles (3.719 – 3.936 kg/m3). The increasing trend of density is mainly attributed to the high value of the atomic mass of the dopants than the tellurite oxide. It is observed that the values of molar volume of the glass samples are increased with increasing concentration of erbium (32.483 – 32.955 m3/mol), erbium nanoparticles (25.868 – 26.737 m3/mol), neodymium (32.258 – 32.612 m3/mol) and neodymium nanoparticles (31.850 – 32.571 m3/mol). The obtained trend is due to the greater value of ionic radii of the dopants than the tellurite oxide. The values of refractive index are found increased with increasing concentration of erbium (1.716 – 1.740), erbium nanoparticles (1.774 – 1.924), neodymium (1.760 – 1.863) and neodymium nanoparticles (1.947 – 2.046). This trend is due to the high value of density. There are several absorption band observed from the UV-Vis spectra of the glass samples which were caused by 4f-4f transitions in erbium, erbium nanoparticles, neodymium and neodymium nanoparticles. The values of optical band gap are decreased along with erbium (3.650 – 3.68 eV), erbium nanoparticles (4.440 – 4.360 eV), neodymium (3.184 – 3.151 eV) and neodymium nanoparticles (3.209 – 3.178 eV) concentration which are due to the high number of free electrons as the number of nonbridging oxygen increases. The non-linear trend of Urbach energy values is obtained in the glass samples (erbium: 0.18 – 0.153 eV, erbium nanoparticles: 0.265 – 2.76 eV, neodymium: 0.316 – 0.320 eV, neodymium nanoparticles: 0.316 – 0.323 eV). The electronic polarizability of the glass samples is increased with increasing content of erbium (5.071 – 5.274 Å), erbium nanoparticles (4.28 – 5.03 Å), neodymium (5.265 – 5.843 Å) and neodymium nanoparticles (6.091 – 6.655 Å). The values of oxide ion polarizability (erbium: 2.185 – 2.148 Å, erbium nanoparticles: 1.77 – 2.02 Å, neodymium: 2.279 – 2.361 Å, neodymium nanoparticles: 2.710 – 2.774 Å) and optical basicity (erbium: 1.195 – 1.181, erbium nanoparticles: 1.012 – 1.004, neodymium: 1.401 – 1.173, neodymium nanoparticles: 1.191 – 1.170) are found in nonlinear variations of all the glass samples. The glass samples are found to be more conductive as the values of metallization criterion (erbium: 0.607 – 5.967, erbium nanoparticles: 0.580 – 0.530, neodymium: 0.589 – 0.549, neodymium nanoparticles: 0.518 – 0.485) increases along with dopants concentrations. The Judd-Ofelt parameters of erbium and erbium nanoparticles doped zinc borotellurite glass are shown to follow the trend of Ω2˃Ω4˃Ω6. Meanwhile, the Judd-Ofelt parameters of neodymium and neodymium nanoparticles doped zinc borotellurite glass are shown to follow the trend of Ω2 ˂ Ω4 ˂Ω6. Green emission is found in erbium and erbium nanoparticles doped zinc borotellurite glasses under 385 nm excitation wavelength. Orange and red emission peaks are found in neodymium and neodymium nanoparticles doped zinc borotellurite glasses respectively. The violet and green emission of upconversion are found in erbium doped zinc borotellurite glass, green emission of upconversion is found in erbium nanoparticles dopant, violet color of upconversion was found in neodymium doped zinc borotellurite glass and blue emission of upconversion is found in neodymium nanoparticles doped zinc borotellurite glass. Erbium and erbium nanoparticles doped zinc borotellurite glasses exhibit negative NLR, meanwhile neodymium and neodymium nanoparticles doped zinc borotellurite glasses exhibit positive NLR. The variations of the NLA of the glass samples are found to be nonlinear.